1994
DOI: 10.1007/bf00009834
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the digestive system of the cercaria of Sanguinicola inermis Plehn, 1905 (Digenea: Sanguinicolidae)

Abstract: The digenean blood fluke Sanguinicola inermis and the family Sanguinicolidae have previously been described as apharyngeate and sucker-less. Examination of the digestive tract of the cercaria of S. inermis with transmission electron microscopy (TEM), however, has confirmed the presence of a well-developed and complex muscular region immediately adjacent to the sub-terminal mouth. The presence of this muscular region, which may be an oral sucker, emphasises the need for further ultrastructural studies on other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The apical projections of the caecal cells become more numerous and acquire a lamellar shape. On the whole, the gut ultrastructure of the fully formed P. borealis cercariae is similar to that of the other digenean larvae studied (Ebrahimzadeh and Kraft 1969;Køie 1971Køie , 1973McMichael-Phillips et al 1994a;Fujino 1997).…”
Section: Discussionsupporting
confidence: 66%
“…The apical projections of the caecal cells become more numerous and acquire a lamellar shape. On the whole, the gut ultrastructure of the fully formed P. borealis cercariae is similar to that of the other digenean larvae studied (Ebrahimzadeh and Kraft 1969;Køie 1971Køie , 1973McMichael-Phillips et al 1994a;Fujino 1997).…”
Section: Discussionsupporting
confidence: 66%
“…The precise way in which the encapsulation response around S. inermis eggs is initiated and operates is not known, although there appears to be a series of stages involved in the response. The egg shell of S. inermis is pale and thin, lacks pores and microspines and is unlikely to be quinone-tanned (McMichael-Phillips et al 1992b). The surface of the egg has shallow reticulations which may aid the passage of immature eggs through the uterus of the adult.…”
Section: Discussionmentioning
confidence: 99%
“…However, the author calles this organ a pharynx. McMichael-Phillips et al (1994) showed the presence of this muscular complex well-developed in cercariae of S. inermis. These authors agreed with Kirk & Lewis (1993) who stated that this muscular element can be an oral sucker, but emphasized the need for further ultrastructural studies on other species of the family.…”
mentioning
confidence: 92%